Treatment of refractory delayed onset heparin‐induced thrombocytopenia after thoracic endovascular aortic repair with intravenous immunoglobulin (IVIG). Issue 1 (19th June 2017) - Doucette, Kimberley; DeStefano, Christin B.; Jain, Natasha A.; Cruz, Allan L.; Malkovska, Vera; Fitzpatrick, Kelly
Abstract: Essentials Delayed‐onset heparin‐induced thrombocytopenia can lead to severe thrombocytopenia in the setting of recent major vascular surgery. Intravenous immunoglobulin (IVIG) can be used as a supplementary treatment when platelet count fails to improve with conventional treatment. When platelet counts are severely low, benefits of using IVIG can outweigh the risks of thromboembolic events. Delayed onset heparin induced thrombocytopenia (HIT), is characterized by a late nadir due to persistent platelet‐activating IgG antibodies. It typically begins or worsens 5 or more days after heparin is discontinued with complications such as thrombosis up to 3 weeks after exposure to heparin. 1–3 In 50% of cases, the platelet count can decrease to very low numbers (<20 000/μL), which is not usual for typical HIT. Here we report 2 cases of post‐operative delayed onset HIT manifesting as severe thrombocytopenia that persisted despite cessation of heparin and initiation of argatroban. Key Clinical Question: Is intravenous immunoglulin beneficial in severe refractory delayed‐onset HIT?